Answer: 8 pi
Step-by-step explanation: So we know that area of a circle is pi times r^2 so if we reverse that formula it would be square root of 16 pi which would be 4 pi and divide by pi so the radius is 4. And we know that the formula for circumference is 2 times pi times r, so 2 times 4 times pi is 8 pi. 8 pi is the cIrcumference! :)
Answer: -2 and -7 i think
Answer:A closed, or shaded, circle is used to represent the inequalities greater than or equal to (≥) or less than or equal to (≤) . The point is part of the solution. An open circle is used for greater than (>) or less than (<). The point is not part of the solution. Solving" systems of linear inequalities means "graphing each individual inequality, and then finding the overlaps of the various solutions". So I graph each inequality, and then find the overlapping portions of the solution regions.Step 1: Line up the equations so that the variables are lined up vertically. Step 2: Choose the easiest variable to eliminate and multiply both equations by different numbers so that the coefficients of that variable are the same. Step 3: Subtract the two equations. Step 4: Solve the one variable system.
Step-by-step explanation:
hope this helps have a great night ❤️❤️❤️
Answer:
your answer would be t=-1 or t=1
Step-by-step explanation:
-(2t-3) = 3t-2
Multiply
-2t+3 = 3t-2
Rearrange and Add up
-5t = -5
Divide both sides by 5
-t = -1
Multiply both sides by (-1)
t = 1
Which is the solution for the Negative Case
Solve the Positive Case
(2t-3) = 3t-2
Rearrange and Add up
-t = 1
Multiply both sides by (-1)
t = -1
have a great day!
The problem is:
![\frac{\frac{3}{x}+\frac{1}{4}}{1+\frac{3}{x}}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Cfrac%7B3%7D%7Bx%7D%2B%5Cfrac%7B1%7D%7B4%7D%7D%7B1%2B%5Cfrac%7B3%7D%7Bx%7D%7D)
We now do L.C.M. of numerator and add, also do L.C.M. of denominator and add together:
![\frac{\frac{12+x}{4x}}{\frac{x+3}{x}}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Cfrac%7B12%2Bx%7D%7B4x%7D%7D%7B%5Cfrac%7Bx%2B3%7D%7Bx%7D%7D)
Dividing by a fraction is same as multiplying by its reciprocal, so we have:
![\frac{12+x}{4x} * \frac{x}{x+3} \\](https://tex.z-dn.net/?f=%5Cfrac%7B12%2Bx%7D%7B4x%7D%20%2A%20%5Cfrac%7Bx%7D%7Bx%2B3%7D%20%5C%5C)
x cancels out, so can multiply and write:
![\frac{12+x}{4} * \frac{1}{x+3} \\=\frac{12+x}{4x+12}](https://tex.z-dn.net/?f=%5Cfrac%7B12%2Bx%7D%7B4%7D%20%2A%20%5Cfrac%7B1%7D%7Bx%2B3%7D%20%5C%5C%3D%5Cfrac%7B12%2Bx%7D%7B4x%2B12%7D)
This is the simplified form.
ANSWER: ![\frac{12+x}{4x+12}](https://tex.z-dn.net/?f=%5Cfrac%7B12%2Bx%7D%7B4x%2B12%7D)